HUKUM DAN MORAL DALAM ADMINISTRASI PEMERINTAHAN DI INDONESIA - Eka Sophia Fitri (Jurnal Hukum Peratun, 2021)
Law and morals are often strictly separated from each other in the modern legal thought of the Kelsenian model. However, its development shows that law is not always separated from morality. Even morality can be used as the basis for the formation of law, although this is not always the case. The writing method used in this research is a normative juridical approach using a statutory approach and a conceptual approach. This paper uses the legal-normative method, namely an approach based on legal materials by examining concepts, theories, legal principles, and legislation, as well as literature related to writing. This paper finds that even in the realm of public law, namely the law of government administration, good morality (goede zeden) is used as the legal basis for the legality of government actions which are positivised in laws and regulations and embodied in the form of general principles of good governance (AUPB).